Industrial Policy: The Role of Government in Promoting Industrial and Technological Development. - Lall, S (United Nations, 1994)
Disillusionment with the role of governments in development has cast doubt on the role of interventions to promote industrialization. Industrial policy is increasingly constrained by this experience and donor pressure. This paper argues that neither the theory of market failure nor the evidence of successful industrialization justifies the present neoliberal stance. The "capabilities" approach to industrial development shows the need for interventions. The experiences of the East Asian NIEs, two Latin American countries and Ghana illustrate the successes and failures of industrial policy. The paper closes with a critique of the World Bank's study of the Asian economic "miracle."